Structural properties and antioxidant activities of soybean protein hydrolysates produced by Lactobacillus delbrueckii subsp. bulgaricus cell envelope proteinase. (1st June 2023) - Zhang, Xiaoying; Huang, Yuyang; Ma, Ruxin; Tang, Yuqing; Li, Yang; Zhang, Shuang
Highlights: Cell envelope proteinase (CEP) extracted from Lactobacillus delbrueckii subsp. bulgaricus . CEP mainly degraded soybean protein near 35 kDa. Hydrolysis time affects structural properties and antioxidant activity of hydrolysates. Hydrolysates after 4 h have the highest antioxidant activity. Abstract: In this work, we investigated the structural and biological properties of soybean protein isolate (SPI) after 0–8 h hydrolyzation with cell envelope proteinase (CEP) extracted from Lactobacillus delbrueckii subsp . bulgaricus. CEP hydrolysis increased the β-sheet and red-shifted the fluorescence peak, while decreasing the α-helix, indicating the unfolding of soybean proteins. Increased surface hydrophobicity and fluorescence of the soybean protein hydrolysates were correlated with the increased hydrophobic amino acid (from 209.67 to 217.6 mg/100 g). CEP tended to hydrolyze the N- and C-terminal regions of sequences dominated by Gly and Leu, which enhanced the antioxidant activity of the SPHs (lowest IC50s value of ABTS + and hydroxyl radical scavenging activity were 0.324 ± 0.006 mg/mL and 0.365 ± 0.001 mg/mL after 4 h hydrolysis). Comparison with the database of bioactive peptides suggested various potential biological activities, including antioxidant activity, angiotensin-converting enzyme inhibitory activity and dipeptidyl peptidase-IV inhibitory activity. The study findings have theoretical significance for the development of CEP hydrolysis and novel bioactive soybean peptides.